Effects of diatom concentration in prepared feeds on growth and energy budget of the sea cucumber Apostichopus japonicus (Selenka). (27th May 2013) - Shi, Ce; Dong, Shuanglin; Pei, Surui; Wang, Fang; Tian, Xiangli; Gao, Qinfeng
Abstract Eight test diets were used in the experiment: seven fresh diatom (Cylindrotheca fusiformis) diets in which diatom occupied 100%, 83.3%, 50%, 33.3%, 20%, 14.3% and 11.1% in dry matter of the feeds (marked as D100, D83, D50, D33, D20, D14 and D11), and a formulated diet (70% Sargassum thunbergii powder, 20% sea mud and 10% fish meal, based on dry weight, marked as ST). The results showed that the specific growth rates (SGRs) of the animals fed diets D33, D20, D14 and D11 were not significantly different from the SGR of those fed diet ST. However, the energy allocated to growth for the animals fed with diet D14 was twice that of diet ST. For sea cucumbers fed diet D14 the largest expenditure part was allocated to respiration (55.4%), but for those fed diet ST, the largest part was allocated to faeces (62.7%). The organic content of diet D14 was also much lower than that of diet ST. Frozen diatom diets containing 14% (dry matter weight) fresh diatom could be an environmentally friendly feed as an alternative option for macroalgae powder.